Buscando componentes da parceria colaborativa na escola entre família de crianças com deficiência e profissionais - Silva, Aline Maira da (Universidade Federal de São Carlos, 2006)
Professionals responsible for education of children with disabilities not always find the way to make their family a partner. This study aims to identify and describe the behaviors of professionals that work in the school and family members that are propitious and maintainers of the effective and successful collaborative partnership. The study was carried out with four focal groups, composed exclusively either by family members or professionals, once there were two groups of family members (FAM1 and FAM2) and two groups of professionals (PROF1 and PROF2) of different schools. 13 family members and 18 professionals participate in the groups. In order to identify the principal components of this partnership two stages were carried out. In each stage two meetings were performed with each focal group, summing up 16 meetings. In Stage 1 the meetings aimed to identify the components of the collaborative partnership, in the first meeting, and to check the collected information in the range group in the second appointment. In Stage 2 each one of the focal groups was collated with the data obtained in the first stage, once family members were paralleled with the professional data and vice versa. The reactions to the data were registered, and afterwards checked in the second appointment. Through qualitative analysis the expected and desired behaviors of professionals and family members were identified and described to increase the probability of success and effectiveness of a collaborative partnership. The categories raised by the family members groups in relation to themselves were: to communicate with the professionals; to be responsible for the child s education; to keep adequate expectations; to accept the children s disability; to respect professionals. On the other hand, the family members expectations about professionals performance were: to communicate with family members; to communicate with other professionals; to be friendly; to separate personal problems from the professional activity; to promote student s development; to be attentive to family problems and to attempt to resolve them; to help family members keep suitable expectations; to incorporate to work suggestions provided by family members; to worry about the student out of school; to offer groups to parents; to respect students and family members; to offer orientation to family members. In their turn, the groups of professionals pointed the following categories in relation to the behaviors they expected of the families: to communicate with the professionals; to recognize the work of the professionals; to trust the developed work; to be responsible for the child s education; to believe in the child s development; to keep adequate expectations; to question the professionals properly; to certify the child s attendance to school; to visit the school; to take part in the activities. Concerning the performance themselves, the following categories were found: to communicate with family members; to show seriousness; to be sincere; to be impartial; to respect students and family members; to be aware of family members and students features; to motivate the participation of family members; to gather with family members; to show the family members the activities performed; to help family members keep suitable expectations. It is expected that, with the survey and the description of the categories, the professionals responsible for the education of children with disabilities and their family members can find their bearings in the search for the establishment of an effective and successful collaborative partnership.
Keywords: Educação especial; Família; Educação - profissionais; Parceria colaborativa; Special education; Family members; Multidisciplinar team; Family-school relation; Collaborative partnership; Children with disabilities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL